ANALISIS KEPUASAN KERJA KARYAWAN PADA CV. ARIVIA JAMBI - Yansen, M. Kashoggie (Jurnal Dinamika Manajemen, 2023)
this study is to determine the Employee Satisfaction CV Arivia In Jambi by analyzing aspects of satisfaction according to EA Locke in Stephen P. Robbins (2003:108) work that is mentally challenged, just compensation, working conditions that support, coworker support. Research methodology used in this research is descriptive analysis using the method of data collection through literature, interviews and questionnaires distribution. Respondents in this study were employees CV Arivia Jambi. The results of this study indicate that overall employees in Edinburgh CV Arivia feel satisfied. The situation is shown by the average percentage of the four aspects, among others, work that is mentally challenged, just compensation, working conditions that support and co-worker support, which get a positive response from employees. From this research, it can be concluded that the employees CV Arivia Edinburgh satisfied in his job, it is seen from the responses of respondents on average were satisfied in the work. Based on this study it can be put forward several suggestions to the management of CV Arivia Jambi, Jambi Arivia CV management should have to pay attention to the factors of satisfaction in working to increase productivity, so it can issue appropriate policies. CV should Arivia Edinburgh in its implementation should always foster employees to work effectively and efficiently to reduce unexpected expenses.